Pengaruh Current Ratio (Cr) dan Debt To Equity Ratio (Der) Terhadap Laba Bersih Pada PT Tempo Scan Pasific Tbk Periode 2012-2022 - Nurwita; Nabila, Nilla (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This study aims to determine the effect of Current Ratio (CR) and Debt to Equity Ratio (DER) on Net Profit at PT Tempo Scan Pasific Tbk for the 2012-2022 period, both partially and simultaneously. This type of research is quantitative and the data sources used are secondary data in the form of financial reports (annual reports), namely balance sheets and income statements. The data analysis technique for this study uses SPSS (Statistical Program For Social Science) Version 24 data processing software. The samples used in this study are balance sheets and income statements published by PT Tempo Scan Pasific Tbk for the 11-year period 2012-2022. Based on the results of the hypothesis test, it shows that the Current Ratio (CR) variable on Net Profit is tcount 3.268> ttable 2.306, meaning that the Ho1 hypothesis is rejected and Ha1 is accepted, thus there is an influence between the Current Ratio (CR) on Net Profit at PT Tempo Scan Pasific Tbk for the 2012-2022 period. Meanwhile, for the variable Debt to Equity Ratio (DER) to Net Profit is tcount 3.378> ttable 2.306 meaning that the Ho2 hypothesis is rejected and Ha2 is accepted, thus there is an influence between Debt to Equity Ratio (DER) to Net Profit at PT Tempo Scan Pasific Tbk for the period 2012-2022. Simultaneously, that Current Ratio (CR) and Debt to Equity Ratio (DER) have a significant effect on Net Profit at PT Tempo Scan Pasific Tbk for the period 2012-2022 with an Fcount value of 6.209> Ftable 4.26. The results of the determination coefficient test show that Current Ratio (CR) and Debt to Equity Ratio (DER) contribute 60.80%. So the remaining 39.20% is influenced by other variables not examined in this study.